Fatigue crack propagation in [0 1 2] NiTi single crystal alloy. (July 2018) - Sgambitterra, E.; Maletta, C.; Furgiuele, F.; Sehitoglu, H.
Highlights: Fatigue crack propagation tests on NiTi single crystal alloy were carried out. DIC technique was used to catch the near crack tip displacement field. Non-linear regression was used to evaluate the effective SIF and crack length. COD measurements were conducted to estimate the near crack tip stiffness. Abstract: Fatigue crack propagation experiments on nickel titanium single crystal alloy, with [0 1 2] crystallographic orientation, were carried out in this study. Stable microstructure, i.e. stable austenite and stable martensite, with the same chemical composition, were investigated. To this aim, two different values of temperature were analyzed. The digital image correlation (DIC) technique was used to obtain the displacement experienced by the sample during the application of the load. Obtained data were used as input parameters of a numerical procedure, that is able to estimate the effective stress intensity factor the sample actually experiences. The procedure is also able to automatically calculate the effective crack length. Numerical crack opening displacement measurements were also conducted in order to estimate the near crack tip stiffness of the microstructures. Results revealed that the stable austenite exhibits a lower threshold value of the stress intensity factor and a higher crack growth rate. Furthermore, it was demonstrated that, when dealing with martensite, local elastic properties change, as a consequence of the variants reorientation, and this effect has to be taken into account for the fatigue crack growth characterization.